The clinical path to integrated genomics in ALL - Bourquin, Jean-Pierre (American Society of Hematology, 2014)
In this issue of Blood, Moorman et al show that most good-risk patients can now be classified robustly by integrating the information from prevalent copy-number alterations (CNAs) in relevant combinations and classical cytogenetic risk factors in acute lymphoblastic leukemia (ALL).(1)